If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + m = 16 Reorder the terms: m + 3x = 16 Solving m + 3x = 16 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-3x' to each side of the equation. m + 3x + -3x = 16 + -3x Combine like terms: 3x + -3x = 0 m + 0 = 16 + -3x m = 16 + -3x Simplifying m = 16 + -3x
| -2.8/7 | | factorisemn=m | | 3(2x-1)=x+27 | | 15-4(2a-1)= | | 3(x-4)=24 | | 4cosx+1=0 | | y=9x^3-7x+2 | | 4c-1=-5 | | 12t=howmenylb | | X+7.1=4.1 | | 3p^2-6p=1 | | 187=88-y | | 1+(4*4)-2= | | S+4.1=8.1 | | 1*10= | | n^2/3-n/6 | | 52x+3=1 | | (3/4)n | | y^2/2=32 | | 9a-8+6a-4= | | 2(3-8)+7= | | y=-5+4sinx | | (5)+(-14)= | | f(x)=-0.91666667*x+1.5 | | (11)+(-3)= | | 6/5cos-1(y/8)=pi | | 16x^6-10x^4/2x^3 | | x-(5x+2)=-4(x-3) | | (-9)+-(14)= | | -x/2*x | | (15)+(-10)= | | 19(8x+3)= |